A single promoter‐TALE system for tissue‐specific and tuneable expression of multiple genes in rice. Issue 9 (24th June 2022) - Danila, Florence; Schreiber, Tom; Ermakova, Maria; Hua, Lei; Vlad, Daniela; Lo, Shuen‐Fang; Chen, Yi‐Shih; Lambret‐Frotte, Julia; Hermanns, Anna S.; Athmer, Benedikt; von Caemmerer, Susanne; Yu, Su‐May; et al.
Summary: In biological discovery and engineering research, there is a need to spatially and/or temporally regulate transgene expression. However, the limited availability of promoter sequences that are uniquely active in specific tissue‐types and/or at specific times often precludes co‐expression of multiple transgenes in precisely controlled developmental contexts. Here, we developed a system for use in rice that comprises synthetic designer transcription activator‐like effectors (dTALEs) and cognate synthetic TALE‐activated promoters (STAPs). The system allows multiple transgenes to be expressed from different STAPs, with the spatial and temporal context determined by a single promoter that drives expression of the dTALE. We show that two different systems—dTALE1‐STAP1 and dTALE2‐STAP2—can activate STAP‐driven reporter gene expression in stable transgenic rice lines, with transgene transcript levels dependent on both dTALE and STAP sequence identities. The relative strength of individual STAP sequences is consistent between dTALE1 and dTALE2 systems but differs between cell‐types, requiring empirical evaluation in each case. dTALE expression leads to off‐target activation of endogenous genes but the number of genes affected is substantially less than the number impacted by the somaclonal variation that occurs during the regeneration of transformed plants. With the potential to design fully orthogonal dTALEs for any genome of interest, the dTALE‐STAP system thus provides a powerful approach to fine‐tune the expression of multiple transgenes, and to simultaneously introduce different synthetic circuits into distinct developmental contexts.